Microwave synthesis of SnO2 nanocrystals on the surface of fine polymer fibers; Inorganic Materials; Vol. 46, iss. 2 - Lysak G. V.; Lysak I. A. Ilya Aleksandrovich; Malinovskaya T. D.; Volokitin G. G. (2010, 2010)
Title screen